Villa Müller. El paseo arquitectónico de Adolf Loos - Neuhaus Buzaglo, Carolina Lucía (2015)
One of the most important works of Adolf Loos is the Villa Müller, where the architect raises the initial ideas of living space in modern architecture, many of which would influence the likes of Le Corbusier. The structural limitations of the time do not stop Loos ´ project to design the open floor plan, and innovate with tours and spatial relationships by the raumplan. This work can be positioned as a forward-looking building, with large contributions to what became the european modern architecture in its consolidation phase. The analysis seeks to find these early ideas, which would then be developed with greater strength due to advances in construction.